English Composition 2 - TR247 - 202300 - Universidad Peruana de Ciencias Aplicadas (UPC) (2023)
English Composition 2 emphasizes rhetoric and research across contexts. Through reading and discussion of content, students engage in rhetorical analysis, research, persuasion, reflection, and revision. It is designed to help students recognize and learn to write for a variety of rhetorical situations, including different audiences, purposes, contexts, and genres. Students will conduct research inquiries, find and evaluate sources, and make critically aware decisions about how best to achieve their purposes. Further, it helps students become aware of their own writing processes and adjust them to whatever demands a particular writing situation places on them.